Habitat Loss Does Not Always Entail Negative Genetic Consequences - Carvalho, Carolina S.; Lanes, Éder C. M.; Silva, Amanda R.; Caldeira, Cecilio F.; Carvalho-Filho, Nelson; Gastauer, Markus; Imperatriz-Fonseca, Vera L.; Nascimento Júnior, Wilson; Oliveira, Guilherme; Siqueira, José O.; Viana, Pedro L.; Jaffé, Rodolfo (Frontiers in Genetics, 2019)
Although habitat loss has large, consistently negative effects on biodiversity, its genetic consequences are not yet fully understood. This is because measuring the genetic consequences of habitat loss requires accounting for major methodological limitations like the confounding effect of habitat fragmentation, historical processes underpinning genetic differentiation, time-lags between the onset of disturbances and genetic outcomes, and the need for large numbers of samples, genetic markers and replicated landscapes to ensure sufficient statistical power. In this paper we overcame all these challenges to assess the genetic consequences of extreme habitat loss driven by mining in two herbs endemic to Amazonian Savannas. Relying on genotyping-by-sequencing of hundreds of individuals collected across two mining landscapes, we identified thousands of neutral and independent single-nucleotide polymorphisms (SNPs) in each species and used these to evaluate population structure, genetic diversity and gene flow. Since open-pit mining in our study region rarely involves habitat fragmentation, we were able to assess the independent effect of habitat loss. We also accounted for the underlying population structure when assessing landscape effects on genetic diversity and gene flow, assessed the sensitivity of our analyses to the resolution of spatial data, and used annual species and cross-year analyses to minimize and quantify possible time-lag effects. We found that both species are remarkably resilient, as genetic diversity and gene flow patterns were unaffected by habitat loss. Whereas historical habitat amount was found to influence inbreeding; heterozygosity and inbreeding were not affected by habitat loss in either species, and gene flow was mainly influenced by geographic distance, pre-mining land cover and local climate. Our study demonstrates that it is not possible to generalize about the genetic consequences of habitat loss, and imply that future conservation efforts need to consider species-specific genetic information.